Choledochal cyst: A case associated with traumatic hemobilia - De Macedo, A. R.; Maffei, H. V L; Viana, H. C. (My University, 1977)
A case of choledochal cyst associated with traumatic hemobilia is presented. The symptomatology appeared only because of bleeding into the biliary tract following an automobile accident. The cyst was resected and a choledochal cystoduodenum anastomosis performed. The early result (12 mth) was very good.
Keywords: bile duct bypass; common bile duct cyst; diagnosis; hemobilia; injury; liver injury; therapy